2000
DOI: 10.1093/oxfordjournals.schbul.a033430
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Deficits and Functional Outcome in Schizophrenia: Are We Measuring the "Right Stuff"?

Abstract: There has been a surge of interest in the functional consequences of neurocognitive deficits in schizophrenia. The published literature in this area has doubled in the last few years. In this paper, we will attempt to confirm the conclusions from a previous review that certain neurocognitive domains (secondary verbal memory, immediate memory, executive functioning as measured by card sorting, and vigilance) are associated with functional outcome. In addition to surveying the number of replicated findings and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,711
8
83

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,733 publications
(1,873 citation statements)
references
References 54 publications
71
1,711
8
83
Order By: Relevance
“…Cognition has been established as a predictor of realworld community functioning in schizophrenia (Green et al, 2000;Evans et al, 2003) and 69% of our sample of psychotic cannabis users reported a social use of cannabis, a similar proportion as in controls. Thus, our findings are compatible with the view that, among psychotic patients, the better premorbid cognition of the group who had smoked cannabis is likely to have facilitated their use of the drug in a normal recreational way, sharing it with their friends.…”
Section: Why Is Lifetime Cannabis Use Associated With Better Premorbimentioning
confidence: 67%
“…Cognition has been established as a predictor of realworld community functioning in schizophrenia (Green et al, 2000;Evans et al, 2003) and 69% of our sample of psychotic cannabis users reported a social use of cannabis, a similar proportion as in controls. Thus, our findings are compatible with the view that, among psychotic patients, the better premorbid cognition of the group who had smoked cannabis is likely to have facilitated their use of the drug in a normal recreational way, sharing it with their friends.…”
Section: Why Is Lifetime Cannabis Use Associated With Better Premorbimentioning
confidence: 67%
“…Cognitive abilities are associated with functional capacity and community outcomes (Evans et al, 2003;Twamley et al, 2002;Patterson et al, 2001;Green and Nuechterlein, 1999;Green, 1996;Green et al, 2000), and may also affect life satisfaction. Poorer cognitive performance and self-reported functional status (e.g., unmarried, lower social functioning, smaller social support network) are correlated with lower subjective QOL (Corrigan and Buican, 1995;Norman et al, 2000;Lehman et al, 1983a).…”
Section: Predictors Of Subjective Qolmentioning
confidence: 99%
“…A global neuropsychological Z-score was calculated from mean Z-scores in four cognitive domains that are impaired in schizophrenia and are related to community functioning outcomes (Green et al, 2000;Heaton et al, 1994;Heinrichs and Zakzanis, 1998): Information processing speed (Trail Making Test, Part A [Reitan and Wolfson, 1993], WAIS-III Symbol Search and Digit Symbol subtests [Wechsler, 1997a]); Working memory (WAIS-III Letter Number Sequencing and Digit Span Backward subtests [Wechsler, 1997a]); Learning (Learning scores from the Hopkins Verbal Learning Test-Revised [Benedict et al, 1998], WMS-III Logical Memory [Wechsler, 1997b], and Brief Visuospatial Memory Test-Revised [Benedict, 1997]); and Executive functioning (Trail Making Test, Part B minus Part A [Reitan and Wolfson, 1993], Wisconsin Card Sorting Test-64 card version [Kongs et al, 2000], Stroop Color-Word Interference Test interference measure [Golden, 1978], Letter Fluency [Benton and Hamsher, 1989]). Lehman, 1988) assessed QOL within the past week globally and within eight domains: living situation, daily activities and functioning, family relations, social relations, finances, work and school, legal and safety issues, and health.…”
Section: Neuropsychological Test Battery-premorbid Verbal Intellectuamentioning
confidence: 99%
“…However, Kraepelin's characterization of schizophrenia from over a century ago included descriptions of cognitive deficits (Kraepelin, 1904), and these have gained greater attention in the treatment literature during the past decade (Green et al, 2000;Weinberger and Gallhofer, 1997). Cognitive deficits found in patients with schizophrenia appear widespread and are related to executive function, working memory, and attention.…”
Section: Introductionmentioning
confidence: 99%